Ч. 2 : Электричество и магнетизм; Физика. Сборник задач (с решениями) - Тюрин Ю. И. Юрий Иванович; Ларионов В. В. Виталий Васильевич; Чернов И. П. Иван Петрович; Антропов Н. А. Николай Андреевич; Борисов В. П. Виктор Петрович; Ботаки А. А. Александр Анджелович; Горячев Б. В. Борис Валентинович; Ефремова Н. А. Наталья Александровна; Купрекова Е. И. Елена Ивановна; Мельникова Т. Н. Тамара Николаевна; Петрова О. Ю. Ольга Юрьевна; Поздеева Э. В. Эльвира Вадимовна; et al. (2010, 2010)
Заглавие с титульного экрана